APPLICATION OF GRADUAL CONCENTRIC CHAMBERS REACTOR FOR LOW-COST DOMESTIC WASTEWATER TREATMENT - Berlian Sitorus (Purifikasi, 2010)
A reactor named gradual concentric chambers (GCC) was designed and evaluated at lab-scale. The system used a set of simple self-supporting containers assembled to create anaerobic and subsequent aerobic treatment of domestic wastewater. The effluent quality of the GCC reactor was compared with a lab-scale Upflow Anaerobic Sludge Bed (UASB) reactor which also treated the same wastewater. The results showed that both GCC and UASB reactors has good organic matter removal efficiency, i.e ± 90%, measured as Chemical Oxygen Demand (COD). The elimination of Total Kjeldahl Nitrogen (TKN) and Total Ammonia Nitrogen (TAN) in the GCC reactor were 57% and 61%, respectively. The final effluent of the GCC reactor had a low turbidity and is odorless due to the combination of anaerobic and aerobic conditions employed in the system. The recovery of biogas from the anaerobic treatment of the GCC compartment was about 20% of the expected volume, while 53% of biogas of the expected amount could be captured in the UASB.